Influence of adittional mass on the cantilever beam to caracteristics bended damping vibration - Karić, Seniha; Nasić, Edis; Pjanić, Merisa (Journal of Production Engineering, 2018)
In this paper a damping rate analysis was performed on the cantilever beam and loaded with an additional mass at the free end. The experimentally obtained results for bending damping vibration of the cantilever have been analyzed. The analysis gives the dependence of the damping factor, measured as the relation of the two adjacent amplitudes, from the moment of inertia, all in a non-dimensional form. It was found that there is an influence of additional mass on the internal damping coefficient for different inertia moment of the cantilever.